Alternative fuels for internal combustion engines - Martins, Jorge (2020)
The recent transport electrification trend is pushing governments to limit the future use of Internal Combustion Engines (ICEs). However, the rationale for this strong limitation is frequently not sufficiently addressed or justified. The problem does not seem to lie within the engines nor with the combustion by themselves but seemingly, rather with the rise in greenhouse gases (GHG), namely CO2, rejected to the atmosphere. However, it is frequent that the distinction between fossil CO2 and renewable CO2 production is not made, or even between CO2 emissions and pollutant emissions. The present revision paper discusses and introduces different alternative fuels that can be burned in IC Engines and would eliminate, or substantially reduce the emission of fossil CO2 into the atmosphere. These may be non-carbon fuels such as hydrogen or ammonia, or biofuels such as alcohols, ethers or esters, including synthetic fuels. There are also other types of fuels that may be used, such as those based on turpentine or even glycerin which could maintain ICEs as a valuable option for transportation.